1996
DOI: 10.1017/s0022215100133614
|View full text |Cite
|
Sign up to set email alerts
|

An audit of prophylactic antibiotic treatment following tonsillectomy in children

Abstract: A prospective audit study was undertaken to assess the effect of two different management policies following tonsillectomy in children in this hospital, one of which requires a prophylactic five-day course of oral antibiotics and the other does not. A total of 95 children were entered into the trial: 54 received post-operative antibiotics and 41 did not. The post-operative recovery was assessed by completion of a parent questionnaire which included the following parameters: degree of patient distress, nausea a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 4 publications
1
29
0
Order By: Relevance
“…The reason given for antibiotic use were consistent with what is reported in the literature: decreased postoperative pain with improved oral intake, and a reduction in mouth odor [20,21]. However, there have been some studies refuting these benefits and noting the disadvantage of potential bacterial resistance [22].…”
Section: Discussionsupporting
confidence: 73%
“…The reason given for antibiotic use were consistent with what is reported in the literature: decreased postoperative pain with improved oral intake, and a reduction in mouth odor [20,21]. However, there have been some studies refuting these benefits and noting the disadvantage of potential bacterial resistance [22].…”
Section: Discussionsupporting
confidence: 73%
“…O'Reilly et al [20], Lee et al [21] found no evidence of reduced secondary haemorrhage rate following routine use of prophylactic antibiotics and question the justification of using prophylactic antibiotic routinely. Dhiwakar et al [22] in their meta-analysis of ten studies in the Cochrane review found no significant reduction in post-tonsillectomy bleeding and the routine use of prophylactic antibiotic.…”
Section: Discussionmentioning
confidence: 99%
“…On further review of the remaining 18 articles, 7 were withdrawn due to a lack of data regarding the primary clinical outcome of interest [9][10][11][12][13][14][15], and 5 were withdrawn due to the absence of a control 856 S. Iyer et al [16][17][18][19][20]. The seven remaining studies with usable information on post-operative outcomes of interest were included in the qualitative portion of this meta-analysis [21][22][23][24][25][26][27]. Of these articles, only four randomized clinical trials met the requirement of both reporting time required for return to normal diet and reporting appropriate measures of significance to allow for a quantitative analysis [21][22][23][24].…”
Section: Trial Flowmentioning
confidence: 99%